Improvement of Sound Acoustic and Compressive Strength of Hybrid Polymer Composites (HPCs) - Ab Malek, Siti Aminah; Wan Jusoh, Wan Amizah (Progress in Engineering Application and Technology, 2025)
This study represents the sound acoustic and compressive properties of the experimentally investigated PALF/polyester hybrid polymer composite with an epoxy resin matrix for sustainable engineering applications. The morphological analysis was done by Scanning Electron Microscopy, and X-ray diffraction was performed for calculating the amorphous and crystalline indices of the materials. Identification of the chemical bonding characteristics was extended using FTIR spectroscopy. Tests carried out in this study used HPCs with variable layers of PALF and polyester fibre mats that were prepared in control, one, two, and three layers in order to investigate their characteristics in terms of sound absorption by the Sound Reduction Index test and their mechanical performance through compressive strength tests at 5 mm/min. These include analysis of physical properties, determining the mechanical behavior, and optimization aimed at getting improved hybrid composite performances. A comparative study regarding acoustic and compressive properties was made to assess their suitability for diversified, sustainable engineering applications. The results obtained in the present work provide an insight into the mechanical properties and eco-friendliness of PALF-and-polyester-based hybrid composite materials, which will be an efficient platform for the development of green and durable engineering applications.